2011
DOI: 10.1084/jem.20100639
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of B7x protects from CD4 T cell–mediated autoimmunity

Abstract: Tissue-specific expression of B7x protects against autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 55 publications
(99 reference statements)
8
93
1
Order By: Relevance
“…It remains unclear what roles B7-H4 play in the periphery, and whether it has functions that are independent of its effect on T cells. We and others have shown that the pancreas expresses moderate level of B7-H4, especially in the endocrine cells [25,27] . This raises the question of what the specific functions of B7-H4 are in pancreatic islets, and suggests the intriguing possibility that activity of B7-H4 is not limited to immune-modulation.…”
Section: B7-h4: a Novel Immune-regulatory Moleculementioning
confidence: 76%
See 2 more Smart Citations
“…It remains unclear what roles B7-H4 play in the periphery, and whether it has functions that are independent of its effect on T cells. We and others have shown that the pancreas expresses moderate level of B7-H4, especially in the endocrine cells [25,27] . This raises the question of what the specific functions of B7-H4 are in pancreatic islets, and suggests the intriguing possibility that activity of B7-H4 is not limited to immune-modulation.…”
Section: B7-h4: a Novel Immune-regulatory Moleculementioning
confidence: 76%
“…Return of glycemic control was observed in newly-onset diabetic NOD mice following B7-H4 Ig injections [33] . Conversely, adoptive transfer of diabetogenic T cells into B7-H4 deficient mice resulted in more exacerbated disease than wild-type controls [27] . It was hypothesized that B7-H4 did not have an effect on recruitment of immune infiltrates during the pre-diabetic stage, but rather, it prevented the progression of insulitis to overt diabetes by arresting severe insulitis at 12 wk of age in NOD mice [27,31] .…”
Section: B7-h4 As a Protective Shield For β-Cells In T1dmentioning
confidence: 90%
See 1 more Smart Citation
“…It is possible that abundant B7-H4 proteins on the surface of tumor cells can impair the effector functions of tumor-infiltrating lymphocytes akin to a molecular shield model proposed for PD-L1 (45,46). In support of this concept, it has been shown that the quantity of B7-H4 on the surface of pancreatic b cells positively correlates with their resistance to T cell attack in murine models of type I diabetes (9). However, our data have shown that, regardless of tumor B7-H4 expression, host B7-H4 still contributes to differences in both proand antitumor immune components, which drives the differences observed in immunoediting between WT and B7-H4 KO mice.…”
Section: Discussionmentioning
confidence: 95%
“…Functionally, engagement of the putative, unidentified B7-H4 receptor on T cells with recombinant B7-H4-Fc proteins in vitro reduced CD4 and CD8 T cell proliferation and cytokine production (1)(2)(3)7). Consistently, B7-H4 knockout (KO) mice displayed elevated Th1 responses against Leishmania major (8) and enhanced Th1 and Th17 responses to experimental autoimmune diseases (9). Interestingly, B7-H4 has also been shown to negatively regulate neutrophil-mediated innate immune responses.…”
mentioning
confidence: 95%